Flowering attributes of Henckelia Royal Queen influenced by pinching and Paclobutrazol application - Wickramasinghe1, NPCH; Seran, TH; Senarathne, MMDJ (Bangladesh Journal of Scientific and Industrial Research, 2021)
An experiment was carried out to determine the effect of pinching practice and different concentrations of Paclobutrazol (PBZ) on the flowering of Henckelia Royal Queen plants.Completely randomized design with eight treatment combinations of pinching or non-pinching and different concentrations of Paclobutrazol (0, 15, 30and 60 ppm) soil drenchwas usedwith eight replicates for each treatment. Pinching was practiced twice at two weeks intervals. Flowering parameters viz. number of flower buds, days taken to flowering, number of flowers, pedicel length, corolla length and corolla width were measured at two weeks intervals from 9thweek after the treatment application. Results disclosed that plants showed better flowering performances (P<0.05) with increasing concentrations of PBZ, but degree of leaf deformation was increased. Therefore, the application of 15 ppm PBZ with pinching showed better to obtain dwarf Henckelia Royal Queen plants with improved flowering quality as commercial potted plants. Bangladesh J. Sci. Ind. Res.56(3), 177-184, 2021